Altern ist Leben - Ist es auch finanzierbar? - Gunther Tichy (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
– The ageing of the European population gave rise to heated discussions. Most participants recommended severe reductions of public pensions, a shift towards a funded system and increased savings of the current generation to reduce the burden of the next one. The paper elaborates five counterarguments: (1) The total burden will not increase much, as the additional pensioners are partly compensated by a reduced number of unemployed. (2) Even with 1 percent growth per capita GDP will be some 60 percent higher in 2050, which should suffice to increase the living standard of the old and the young. (3) The real burden cannot be shifted, and a shift of the financial burden can prove counterproductive. (4) The pay-as-you-go system should not be abandoned, as it covers wider and more severe risks than a funded one. (5) Surveys show clearly that the population appreciates a public pension scheme and prefers higher contributions to reduced pensions.
Keywords: H55; J11; J14; J26; 330